2019
DOI: 10.3390/antiox9010031
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Slow-Releasing Hydrogen Sulfide Donors in the Mechanical Allodynia, Grip Strength Deficits, and Depressive-Like Behaviors Associated with Chronic Osteoarthritis Pain

Abstract: Osteoarthritis and its associated comorbidities are important clinical problems that have a negative impact on the quality of life, and its treatment remains unresolved. We investigated whether the systemic administration of slow-releasing hydrogen sulfide (H2S) donors, allyl isothiocyanate (A-ITC) and phenyl isothiocyanate (P-ITC), alleviates chronic osteoarthritis pain and the associated emotional disorders. In C57BL/6 female mice with osteoarthritis pain induced by the intra-articular injection of monosodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 52 publications
9
25
0
1
Order By: Relevance
“…In agreement, we have previously described that GYY-4137 decreased the expression of pro-inflammatory markers in chondrocytes by an in vitro experimental approach [ 19 ]. Besides this, other authors have also detected the capacity of H 2 S to reduce the levels of inflammatory mediators in the joint in in vivo studies [ 27 ] [ 44 , 46 ]. iNOS and COX-2 are enzymes responsible for the synthesis of NO and PGE 2 , respectively, which are widely known to be key mediators that contribute to the pain and pathogenesis of OA [ 6 , 51 ].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In agreement, we have previously described that GYY-4137 decreased the expression of pro-inflammatory markers in chondrocytes by an in vitro experimental approach [ 19 ]. Besides this, other authors have also detected the capacity of H 2 S to reduce the levels of inflammatory mediators in the joint in in vivo studies [ 27 ] [ 44 , 46 ]. iNOS and COX-2 are enzymes responsible for the synthesis of NO and PGE 2 , respectively, which are widely known to be key mediators that contribute to the pain and pathogenesis of OA [ 6 , 51 ].…”
Section: Discussionmentioning
confidence: 94%
“…This is despite the fact that the intraarticular injection of saline has also shown some beneficial effects, as it is now considered to be effective at alleviating nociceptive pain and in turn is not a true placebo in OA [ 40 ]. Accordingly, Batalle et al (2019) observed that the systemic administration of slow-releasing H 2 S donors reduces mechanical allodynia and the grip strength deficits induced by the intraarticular injection of monosodium iodoacetate (MIA) in mice [ 27 ]. Lucarini et al (2018) also demonstrated the antinociceptive effects of different compounds exhibiting slow H 2 S-release properties in an osteoarthritic pain model [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations